Influence of coal-fired power plant combustions toward neighbourhood residents - Mohd. Din, Shamzani Affendy; Nik Yahya, Nik Nurul Hidayah; Othman, Rashidi; Abdullah, Alias (American Scientific Publishers, 2017)
Generally, human spend about 30–90% of their daily time indoor. Therefore, permanent and temporary residential area located surrounding the coal-fired power plant should be the today’s major concern. This is for the escalate uncontrol number of the coal-fired power plant and urbanisation with numbers of residential area surrounding its location that can provide high health risk towards its occupiers. The inhalable and respirable dust sample are collected at three residential with the radius of 5 km, 15 km, and 20 km to the coal-fired power plant.This sample are then digested and analysed with the high sensitive ICPMS (Nexion 300×) on the concentrations of Ba, Cr, Cu, Fe, Mn, Ni, Pb, V, and Zn in both respirable and inhalable particles Results shows that 50.55% of respirable dust towards inhalable dust at outdoor and 52.94% for indoor samples collected at residential area 20 km to point-source. Thus, suggesting that indoor air quality in Sitiawan occupied higher risk for human health rather than the outdoor atmospheric ambient. At the residential area of 15 km to point-source, the indoor ratio of respirable towards inhalable dust are higher than the outdoor ambient. In comparison between outdoor ratios, it can be found that the ratio is decreasing at outdoor ambient as the distance increase from the coal-fired power plant. The mean ranges of respirable dust found collected at a residential nearby coal-fired power plant in Manjung are between 0.0345 and 84.128 mg m−3. Higher ranges are found average in the inhalable dust at 0.0483 and 81.890 mg m−3. Thus, sum up to an overall average for all metal concentrations at 42.081 and 40.969 mg m−3, for respirable and inhalable dust, accordingly. The dominant metals for all sampling locations in residentials are Fe, Zn, and Ni. The highest is Fe for both inhalable dust and respirable dust at 82.506 and 139.900 mg m−3, correspondingly. Hence, suggesting the amount of ratio respirable towards inhalable dust at 50.67%.